2016
DOI: 10.1590/1678-775720150524
|View full text |Cite
|
Sign up to set email alerts
|

Tissue dissolution and modifications in dentin composition by different sodium hypochlorite concentrations

Abstract: Sodium hypochlorite (NaOCl) remains the most used irrigation solution during root canal preparation because of characteristics such as wide-spectrum antimicrobial activity and organic tissue dissolution capacity. However, these solutions can alter dentin composition and there is no consensus on the optimal concentration of NaOCl to be used. Objectives To determine the organic matter dissolution and changes in dentin chemical composition promoted by different concentrations of NaOCl over time. Material and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 34 publications
(58 reference statements)
5
68
0
11
Order By: Relevance
“…Craig et al and Rautiola and Craig observed that the microhardness of dentin tends to increase as it distances from the dental pulp . Thus, knowing that the microhardness is related to the inorganic matrix, we can assume that the lower proportion of inorganic content in the intracanal region causes an imbalance in the ionic exchanges that occur between phosphate and carbonate, making the dentin more soluble and susceptible to the loss of ions to the artificial saliva . The lower concentration of carbonate favors the development of caries lesions .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Craig et al and Rautiola and Craig observed that the microhardness of dentin tends to increase as it distances from the dental pulp . Thus, knowing that the microhardness is related to the inorganic matrix, we can assume that the lower proportion of inorganic content in the intracanal region causes an imbalance in the ionic exchanges that occur between phosphate and carbonate, making the dentin more soluble and susceptible to the loss of ions to the artificial saliva . The lower concentration of carbonate favors the development of caries lesions .…”
Section: Discussionmentioning
confidence: 98%
“…Thus, knowing that the microhardness is related to the inorganic matrix, we can assume that the lower proportion of inorganic content in the intracanal region causes an imbalance in the ionic exchanges that occur between phosphate and carbonate, making the dentin more soluble and susceptible to the loss of ions to the artificial saliva . The lower concentration of carbonate favors the development of caries lesions . This imbalance is related to the lower degree of mineralization and higher density of tubules in the intracanal root dentin region, which also justifies the nonalteration of carbonate in the middle root dentin region.…”
Section: Discussionmentioning
confidence: 99%
“…The initial infrared absorbance spectrum of the samples was obtained over the range of 4000-400 cm À1 at 1 cm À1 resolution using 32 scans and was recorded using the OMNIC Spectra Software. Thereafter, the samples were distributed into four groups (n = 5) and were subjected to irrigation protocols as previously described (Tartari et al 2016). In the first set of experiments, the samples of one group were dipped individually in microtubes containing 1.5 mL of 2% CHX solution for 30 s and ultrasonicated for 15 s. Subsequently, they received a flush in a microtube with 1.5 mL of distilled water for 1 min of which 15 s were under ultrasonic agitation.…”
Section: Ftir Analysismentioning
confidence: 99%
“…,, Tartari et al . ). By monitoring changes in the IR absorption frequencies following NaOCl exposure, it may be possible to assess the depth of any changes due to root canal irrigation.…”
Section: Introductionmentioning
confidence: 97%